Análise metabolômica de alterações induzidas pelo vírus mayaro em células vero - Castro, Ceyla Maria Oeiras de (2015)
This study aimed at assessing the extracellular metabolic profile of Vero cells infected by Mayaro virus. In this metabolomic study, the use of nuclear magnetic resonance associated to multivariate analytical methods, devices of standard recognition, showed metabolic variations which can be attributed to the effect of Mayaro virus infection. Vero cells were infected and incubated for 2, 6 and 12 hour periods. Differentiated variations in the levels of several metabolites such as amino acids, organic acids, guanidine compound, monoamine, carbohydrates and fatty acids have occurred in each period. These organic compounds are metabolites involved in the glycolysis pathway, tricarboxylic acid cycle, pentose phosphate pathway, and the oxidation pathway of fatty acids (via the β-oxidation). This study demonstrates footprinting analysis representing the effect of the virus action on the Vero cell metabolism, furthermore, these analyzes point out the intracellular metabolic state, improving the knowledge of the microorganism influence on cellular metabolism.